Teacher Training For Making HOT (Higher Order Of Thinking) Tests - Nurul Wati (Asian Journal of Science Education, 2019)
Higher Order Of Thinking (HOT) based tests are very necessary for students, because in addition to increasing student understanding, HOT-based learning instruments can also improve the abilities and skills possessed by students. The purpose of this training is to hone the teacher's skills in preparing HOT-based tests and find out the participants' responses to the activities carried out. The stages of community training activities are: coordination of the implementation team with partners and LPPM Unsyiah, preparation of materials, identification of problems by partners, training of teachers, data analysis and reporting of activities. The subject of this training is Physics Teacher at the SMA Negeri 1 Meulaboh. The target of this activity is to equip partner teachers with basic knowledge and experience in developing HOT-based tests, able to properly compile HOT-based physics questions. The outputs produced are (1) service report; (2) HOT question preparation module and (3) Articles that will be published in the Journal. The results of the training activities carried out went well, targets that had been set previously had been achieved well. Physics teachers already have the knowledge to develop HOT-based questions and will continue to develop further. Through the results of the questionnaire analysis the responses of the participants obtained good responses. Where the physics teacher at SMA Negeri 1 Meulaboh felt helped by the existence of this training activity and wanted to be applied in the learning process.